Worldmark encyclopedia of the states. - Gale Group (Farmington Hills, Mich. Gale, Cengage Learning, 2016)
Details current geographical, social, and political data, historical narrative, and statistical information on the 50 states, District of Columbia, Puerto Rico, and Caribbean and Pacific dependencies of the United States. Maps, tables, flags and official state seals are included.
volume 1. Alabama to Montana -- volume 2. Nebraska to Wyoming, and District of Columbia, Puerto Rico, U.S. dependencies, and U.S. overview.
Includes bibliographical references.
Keywords: U.S. states -- Encyclopedias; United States -- Territories and possessions -- Encyclopedias; United States -- Encyclopedias